Integração lavoura pecuária: procedimentos agronômicos para o uso de herbicidas no consórcio de milho e papuã - Oliveira, Juliano Rossi (2013)
In the Southern Brazil, Crop Livestock systems shows a critic period of forage availability in the transition period between summer and winter seasons. Intercrop systems, using grain crops and forage plants are an alternative to avoid this forage deficit. Among the factors that could favor this system adoption, its highlighted the high spread of Alexandergrass (Brachiaria syn. Urochloa plantaginea) in the corn fields, a grass that present high forage production of good quality. However, to the intercropped system with corn plus Alexandergrass result in good productivity for both species, it is necessary to consider the reduction of forage plant initial development by spraying herbicides. It will ensure that the competition between the species do not reduce the corn production. Thus, the aim of this study was to evaluate herbicide managements and their influence over corn grain production and Alexandergrass dry mass production, in an intercropped system. The study was carried out from October 2011 to May 2012, at the Experimental Unit of IAPAR (Instituto Agronômico do Paraná), in Pato Branco – PR, Brazil. The experiment was laid out in a randomized block design, with four replications. The studied factors were three herbicide associations, and an herbicide treatment: (1) Atrazine + Oil; (2) Atrazine + Simazine + Oil; (3) Atrazine + Nicosulfuron + Oil; (4) Atrazine + Mesotrione + Oil, and three levels of these herbicide associations: 100%, 75% and 50% of the recommended dose to the total control of Alexandergrass. It was evaluated a control treatment with the corn crop without Alexandergrass management. Forage plant establishment occurred by natural reseeding. Corn crop was sown by a no-till seed planter on October 4th, 2011. The herbicide was sprayed at October 18th, 2011. Results show that herbicide management was necessary to obtain good productions of booth intercropped species. At the control treatment, without herbicide application, corn grain yield was drastically reduced (67%). Corn yield increased as herbicide level increases, and Alexandergrass dry matter production decreased as herbicide levels increased. Despite de herbicide management, it was possible to obtain forage to graze or harvest during the deficit period between the summer and winter seasons. However, Alexandergrass dry mass production was influenced by the herbicide types and doses. Mesotrione plus Nicosulfuron resulted in the highest corn yields. Atrazine plus Simazine resulted in the higher Alexandergrass dry mass production. The association of Atrazine + Mesotrione + Oil at 75% of the recommended dose resulted in low interferences in corn development, good corn grain yield and forage production, highlighting as one of the best herbicide managements that allowed good productivity of both species at the same time.